Shape and Chronology of Wooden Coffins in Mamasa, West Sulawesi, Indonesia - Duli, Akin (TAWARIKH, 2014)
ABSTRACT: Toraja-Mamasa ethnic is one of ethnics that dwell in Mamasa Regency, West Sulawesi Province, Indonesia. They have inhabited the region from ancient times until now and have a variety of uniquely cultural forms, and it is interest to study. One form of cultures that characterize the culture of Mamasa is a burial system placed in a limestone hills with wooden coffins. There have been no archaeological experts who examined the wooden coffin in the region; so, the distribution of site, form, layout, dating, and cultural significance is not known scientifically. Therefore, it is necessary to study archeologically to understand the various aspects before it destroyed, and becomes extinct of natural processes such as weathering and damaged by treasure seekers. The research of wooden coffin in Mamasa region, West Sulawesi, Indonesia was conducted by a systematic survey and sampling methods for radiocarbon dating. The study found 21 sites with a dozen pieces of coffins, which consists of boat-shaped or âbangka-bangkaâ, buffalo-shaped or âtedong-tedongâ, horse-shaped or ânarangâ, round-shaped or âtalukunâ, and house-shaped tomb or âbatutu. Wooden coffin burial sites are always located not far from villages, rice fields or gardens, and located in the south or southwest of the old village. The lay outs of the coffins are always on the sand stone hills with south or west orientation. Differences in shape, layout, and orientation are strongly influenced by factors of trust, cosmology, and social stratification concept. The dating results shows that wooden coffins have been used since 730 Â± 50 BP or about 1200 AD (Anno Domini) and keep continue until the 1970âs. KEY WORDS: Wooden coffin, Mamasa community, radiocarbon dating, differences in shapes, trust, cosmology, and social stratification concept.About the Author: Dr. Akin Duli is a Senior Lecturer at the Department of Archaeology, Faculty of Humanities UNHAS (Hasanuddin University) in Makassar City, South Sulawesi, Indonesia. For academic purposes, he can be reached at: akinduli@yahoo.co.idHow to cite this article? Duli, Akin. (2014). âShape and Chronology of Wooden Coffins in Mamasa, West Sulawesi, Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.5(2) April, pp.177-186. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 23, 2014); Revised (March 27, 2014); and Published (April 28, 2014).